Evaluation of bleaching efficacy, microhardness, and trans-amelodentinal diffusion of a novel bleaching agent for an in-office technique containing hexametaphosphate and fluoride - Nunes Júnior, Nilson Antônio [UNESP] (2022)
Objective: This study evaluated in vitro the effects of calcium gluconate (CaGlu), sodium fluoride (NaF), sodium hexametaphosphate (HMP), and NaF/TMP added to a 35% hydrogen peroxide (H2O2) bleaching gel on the color change, enamel hardness, and trans-amelodentinal diffusion. Materials and methods: Enamel discs/bovine dentin (n = 150) were divided according to the bleaching gel: 35% H2O2 (H2O2); 35% H2O2 + 0.1% NaF (H2O2/NaF); 35% H2O2 + 1% HMP (H2O2/HMP); 35% H2O2 + 0.1% NaF + 1% HMP (H2O2/NaF/HMP), and 35% H2O2 + 2% CaGlu (H2O2/Caglu). The bleaching gels were applied three times (40 min/session) at 7-day intervals between each application. Then, color alteration (ΔE), whitening index (ΔWID), percentage of surface hardness loss (% SH), cross-sectional hardness (ΔKHN), and trans-amelodentinal diffusion were determined. Data were submitted for analysis of variance (ANOVA), followed by the Student–Newman–Keuls test (p < 0.05). Results: All bleaching gels showed significant color changes after treatment (p < 0.001). ΔE and ΔWID were similar among the evaluated gels. Mineral loss (% SH and ΔKHN) and trans-amelodentinal diffusion of hydrogen peroxide were lower for H2O2/NaF/HMP; the H2O2/CaGlu group presented the highest values about the other groups (p < 0.001). Conclusion: It is possible to conclude that the addition of NaF/HMP to the in-office bleaching agent did not interfere with the bleaching efficacy and reduced enamel demineralization and H2O2 diffusion. Clinical significance: The association of NaF/HMP to the bleaching gel can be used as a novel approach for minimizing the adverse effects of H2O2 by-products and with similar clinical efficacy.